EFFECTIVENESS OF USING THE ACHIEVEMENT PROFILE (PORTFOLIO) AS AN ALTERNATIVE ASSESSMENT TOOL IN THE ACHIEVEMENT OF LITERARY FIFTH GRADE STUDENTS IN THE ARABIC LANGUAGE SUBJECT - Dr: Mushtaq Fakher Daidan Odeh; Dr. Ali Hamza Hadi Hilal (Scholars Digest Publishing, 2023)
This study aims to determine the use of achievement profiles (Portfolio) as an alternative assessment tool for fifth grade literature students' achievement in the Arabic language subject. The study followed the experimental approach of a front-to-back design with two equal groups. The study sample consisted of (68) fifth grade literature students who were selecting for boys. Researchers prepare research tools Test the hypothesis using appropriate statistical means, namely a T- Test of Two Independent Samples, T-Test of Two Related Samples, and the equation for the ATA box; to determine the size of the effect. The results showed that there was a statistically significant difference between the experimental groups using grades. (achievement test), which consists of (30) items of the MCQ type, and verify its validityvalidit reliability and psychometric characteristics, profile (Portfolio) in its teaching at the expense of the control group, and it was also found that there was effectiveness in employing the achievement profile (Portfolio) in increasing achievement
Keywords: Achievement Profile (Portfolio) , Alternative Assessment , Achievement , Arabic language.